Global research hotspots and trends in the application of artificial intelligence in gastric cancer: a bibliometric analysis from 2005 to 2024 - Chen, Lu; Zhao, Jinying; Liu, Zijian; Kong, Lingzu; Zhou, Dan; Wang, Fuchun (Frontiers in Oncology, 2025)
BackgroundGastric cancer (GC) is a prevalent gastrointestinal malignancy. In recent years, the application of artificial intelligence (AI) in GC has become increasingly widespread. This study aims to employ bibliometric analysis to offer valuable insights for researchers.MethodsPublications concerning the application of AI in GC between 2005 and 2024 were retrieved from the Web of Science Core Collection. Subsequently, VOSviewer, CiteSpace, and Scimago Graphica were employed to conduct the bibliometric analysis of the selected literature.ResultsA total of 903 publications were included in this study. In the past two decades, the application of AI in GC has become more widely used, and the number of papers published has shown a rapid growth trend. China, Japan, and South Korea are the most prolific countries in this field. Yonsei University, the Chinese Academy of Sciences, and Shanghai Jiao Tong University are the three institutions with the most publications. Surgical Endoscopy and Other Interventional Techniques is the most published journal and also the most cited journal. Woo Jin Hyung from Yonsei University is both the most prolific author and the author with the highest H-index. Gastric cancer, surgery, and artificial intelligence are the three keywords most used. The keywords “upper gastrointestinal endoscopy” and “artificial intelligence” have been prominent until now.ConclusionThis study offers a comprehensive visual overview of the application of AI in GC over the past two decades. AI-assisted screening, diagnosis, and prognosis prediction in GC are anticipated to represent focal points of future research in this domain.